ANALISIS KEPEMIMPINAN KUALITAS PADA PENDIDIKAN TINGGI - Mudzakir, Mudzakir (potensio, 2012)
Leadership quality in higher education is a leader who has a qualification that is able to perform both quality management and quality as a measure of success. In his leadership must be able to perform all the functions of leadership. Leaders who implement TQM programs in higher education should be able to create a quality culture that encourages all members to satisfy the customers. Benchmarking is the best practice for quality improvement in higher education. The success in the application of benchmarking depends of the ability of higher education organization leaders. Quality leadership depends on its ability to adopt the five stages and strategies. basic instruments of quality improvement using the theory of The Basic Quality Improvement Tools which includes ten instruments/Keywords: Leadership Quality, TQM, Benchmarking